Tobacco smoking perception and practice among pre-university students in a government boy’s college: a cross sectional study - Basagoudar, Shashidhar S.; R., Chandrashekhar; Hatanoor, Shivappa; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco is the single most preventable cause of death in the world hence this study was aimed at detecting the prevalence of tobacco smoking among students of a government pre-university college for boys, to find out the perception of students about tobacco smoking and factors related to the tobacco smoking among students. Methods:A cross sectional study conducted among purposively selected students of Government Pre-university College for boys. Data was collected through pre-structured questionnaire. Tobacco smoking was assessed by self reporting by filling the questionnaire. Results: The prevalence of ever use of tobacco smoking was 13.7% and current smokers were 5.6%. Mean age of starting smoking was 14.16 yrs. 66% of students were aware that tobacco smoking can lead to cancer. In majority (81.1%) of ever smoked students, their friends have motivated them to smoke for the first time. 93% of students knew that passive smoking is injurious to health. 83% of students felt that tobacco should be banned. Having a smoker in the family (p=0.035) and a student residing away from parents (p=0.007) are positively associated with ever smoking tobacco. Conclusions:Tobacco smoking is prevalent among the boys of government pre-university college students. Majority of students have better perception about tobacco smoking. Familial support and peer involvement are crucial in controlling the tobacco smoking.